The contribution of museums to preserving heritage and Algeria's civilizational development: A case study of the Museum of Ancient Antiquities and Islamic Arts - Mokhtaria, Mokaddem; Bentnebi, Mokaddem (The International tax journal, 2025)
Algeria abounds with numerous archaeological sites that testify to its history of successive ancient civilizations. These have left a wealth of archaeological remains, reflecting the interaction and blending of cultures throughout the ages. These imprints that inspire us to be explored; they are embodied in the remains of buildings, pottery vessels, coins, mosaic panels, inscriptions, sculptures, and other archaeological findings. These artifacts are often preserved in museums, which work to safeguard the historical and civilizational heritage of any civilization. Where do we stand concerning the heritage accumulated in museums? How can we highlight and preserve it using scientific methods? What is the role of the museum in society? And how can we utilize it in ways that align with human development to support the national economy?